ENGLISH COLOUR LEXEMES IN J. K. ROWLING’S NOVELS - Mykytiuk, Iryna; Lesinska, Oksana (Advanced Education, 2019)
The article explores lexical units denoting colour in English. The study focuses on colour lexemes in a literary text in terms of their combining potential, structure, and stylistic properties. The undertaken analysis of 11 basic colour lexemes (black, white, grey, red, blue, orange, yellow, green, purple, pink, brown) testifies to their combinability with twelve thematic word-groups that denote: appearance, footgear, dress, headgear, fauna, flora, parts of the body, natural phenomena, objects, magic, substances, food. Sixteen non-basic colour lexemes (sallow, auburn, blank, swarthy, silver, livid, scarlet, gold / golden, blond, amber, emerald, aquamarine, violet, lilac, turquoise, crimson) demonstrate combinability with only five thematic word-groups: appearance, objects, magic, dress, substances. The prevailing usage of the basic colour lexeme black and non-basic colour lexeme gold / golden is explained by the general magical atmosphere created by J. K. Rowling in the novels featuring adventures of the young sorcerer Harry Potter. The analysis of word-building specificity of colour lexemes proves that compounding of the pattern Adj+Adj (white-blond; golden-brown; light-blue) is the predominant way of their formation. Stylistic devices involving colour lexemes in the analysed literary texts are used with the aim to enhance the expressiveness of the narrative pieces, provide additional characteristics to the people and objects described, produce a humorous effect, and arrange the rhythmical pattern of the utterances. Rowling’s choice of certain colour lexemes is illustrative of her individual author’s style.